Análise de parâmetros de força na dinamometria de nado atado e semiatado - Rafael Soncin Ribeiro (2012)
The propulsive force of swimming and technique are key factors in the performance of swimmer. The more specific methods to evaluate the propulsive force dynamometry are fully tethered swimming and partially tethered swimming. The regression models known to evaluate the dynamometry of the fully tethered swimming (R1) and partially tethered swimming (R2) consider only the mean force produced in each test. The purpose of the study was to propose a regression model for each dynamometer test, considering the force variation around the average for the fully tethered swimming (R3) and the pre-established velocity of the partially tethered swimming (R4). Twelve swimmers (21.8 ± 4.4 years, 1.77 ± 0.07 meters, 70.6 ± 5.4kg, 26.3 ± 1.9s as the best time in the 50 meters free swimming) with more than five years of experience in this sport performed in a random order the free swimming, dynamometry of the fully tethered swimming and of the partially tethered swimming. The results for R1 and R3 presented similar values for the r2 (0.7436 and 0.7539, respectively), however, in R1 the intercept was significant different from zero. This suggests that the oscillation parameter comprised part of the mean velocity that was previously considered as an independent term of the equation. R4 presented a higher r2 (0.9002) than R2 (0.5975), possibly because it was the only model that effectively considers the drag force on the swimmer and he velocity of the test. In that way, the proposed models, R3 and R4, seem to be more efficiently to evaluate the results obtained by the dynamometer tests.